Trichodina heterodentata (Ciliophora: Trichodinidae): a new parasite for Piaractus mesopotamicus (Pisces: Characidae) - de Pádua, Santiago Benites; Martins, Maurício Laterça; Carraschi, Silvia Patrícia; Da Cruz, Claudinei; Ishikawa, Márcia Mayumi (Zootaxa, 2012)
Trichodinids are mobile peritrichous ciliated protozoa, and widely known as ectocommensals and/or parasites of fish andother aquatic organisms. Little is known about the trichodinid fauna in Brazilian fish. This study reports Trichodina het-erodentata Duncan, 1977 as a new parasite for freshwater fish Piaractus mesopotamicus Holmberg, 1887. This is the firstrecord of this trichodinid in southeastern Brazil. Fifty specimens impregnated with 2% silver nitrate and another fiftystained with Giemsa were used for morphometry on the taxonomic characteristics. T. heterodentata in this study is medi-um size, with a disc-shaped body measuring 49.0 to 61.0 µm, parasitizing the skin, fins and gills of pacu. Measurement comparisons between the present material and other records from different countries are presented.